2023
DOI: 10.1002/gea.21972
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing formation processes at the Canary Islands indigenous site of Belmaco Cave (La Palma, Spain) through a multiproxy geoarchaeological approach

Abstract: The indigenous populations of La Palma (Canary Islands), who arrived on the island from Northwest Africa ca. 2000 years B.P., were predominantly pastoralists. Yet, many aspects of their subsistence economy such as the procurement, management, and use of wild plant resources remain largely unknown. To explore this, we studied the 600–1100‐year‐old archaeological site of Belmaco Cave, which comprises a stratified sedimentary deposit representative of a fumier. Here, we present a high‐resolution, multiproxy geoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…The formation of the hazenite mineral in Mono Lake, investigated by Yang et al ( 2014 ), has been linked to the metabolic activity of cyanobacteria of the genus Lyngbya and occurs in the presence of carbonates (Yang et al, 2011 ). Hazenite has been observed for the second time at the Belmaco Cave site (La Palma, Spain) (Fernández-Palacios et al, 2023 ). Although earlier studies have suggested that cultures containing the bacterial strain Virgibacillus sp can prompt the precipitation of an ammonium analog of hazenite, specifically (NH4)NaMg 2 (PO4) 2 ·14H 2 O (Yang et al, 2014 ), for as much as we know, this is the first report of hazenite synthesis with K and Na, mediated by heterotrophic bacteria under controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the hazenite mineral in Mono Lake, investigated by Yang et al ( 2014 ), has been linked to the metabolic activity of cyanobacteria of the genus Lyngbya and occurs in the presence of carbonates (Yang et al, 2011 ). Hazenite has been observed for the second time at the Belmaco Cave site (La Palma, Spain) (Fernández-Palacios et al, 2023 ). Although earlier studies have suggested that cultures containing the bacterial strain Virgibacillus sp can prompt the precipitation of an ammonium analog of hazenite, specifically (NH4)NaMg 2 (PO4) 2 ·14H 2 O (Yang et al, 2014 ), for as much as we know, this is the first report of hazenite synthesis with K and Na, mediated by heterotrophic bacteria under controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies define hazenite as the first struvite-type compound containing two structurally distinct monovalent cations (K and Na), indicating an exclusive role of the biological activity in the mineralization process (Yang et al, 2011 ). Hazenite has been observed for the second time at the Belmaco Cave site (La Palma, Spain) (Fernández-Palacios et al, 2023 ). To date, these two sites appear to be the only ones where this biomineral has been identified.…”
Section: Introductionmentioning
confidence: 99%